ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENJADI ENTREPRENEUR (Studi pada Mahasiswa Fakultas Ekonomi Universitas Surakarta) - Widiastuti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The purpose of this study was to determine and quantify the effect ofvariable tolerances of the risks, the success of self, freedom of work, and thebackground of parents work either partially or simultaneously against theinterests of students into entrepreneur. In this study, the population isSurakarta University students who already take entrepreneurship courses.Based on data obtained from the Head of the Academic Faculty ofEconomics, University of Surakarta in 2013 – 2015 amounted to 718students, while the sample is taken as many as 71,8 (72) respondents.Hypothesis analysis tools used in this study are: the classic assumption test,linear regression, t-test test, test F-test and coefficient of determination. Theresults of data analysis using SPSS version 21.0 for classical assumption,that the test for normality, autocorrelation, multicollinearity, andheteroscedasticity, shows all the variables used in this study has escapedfrom the classical assumption test. In terms of significance, seen from the ttest, that tolerance of risk (X1), the success of the self (X2), Freedom in theworks (X3), and the background of their parents' job (X4) partially positiveinfluence and significant impact on student interest into entrepreneur (Y).Furthermore, seen from the F test, proved that tolerance of risk (X1), thesuccess of the self (X2), the freedom to work (X3), and the background oftheir parents' job (X4) simultaneously affect positive and significant impacton student interest into entrepreneur (Y) , Judging from the magnitude of thecoefficient of determination (adjusted R square) which has a positive value of0,821, indicating that the interest of the students to be explained by thevariable entrepreneur will risk tolerance, personal goals, freedom in workand educational background of the parent amounted to 82,1% and thebalance of 17,9% describe their other variables that are not observed in thisstudyKeywords: tolerance of the risks, the success of self, freedom of work, thebackground of the work of parents, student interest intoentrepreneur.